Investigation of the Effects of Evaporation Methods on the High-Temperature Rheological and Fatigue Performances of Emulsified Asphalt Residues. (16th March 2020) - Sun, Yang; Yue, Jin-Chao; Wang, Ri-Ran; Li, Rui-Xia; Wang, De-Cai
Abstract : Cold recycling technology is a widely applied asphalt pavement rehabilitation technology. The properties of emulsified asphalt residues after water evaporates play an important role in the performance of the asphalt pavement. This paper investigates the rheological and fatigue properties of emulsified asphalt residues under different evaporation methods. Two different matrix asphalt binders and emulsifiers were selected to prepare the emulsified asphalt. Moreover, the direct heating method (DHM) and the EN13074 and ASTM D7497-09 evaporation methods were used to obtain emulsified asphalt residues. Furthermore, the linear viscoelasticity, the permanent deformation resistance, and the fatigue resistance were evaluated by the temperature sweep and frequency sweep tests, the multiple stress creep recovery (MSCR) test, and the linear amplitude sweep (LAS) test, respectively. The test results show that under the three evaporation conditions, the growth amplitude order of the rutting factor, recovery percent, complex modulus, and fatigue life of emulsified asphalt residues is ASTM D7497-09 > EN13074 > DHM, and as is the attenuation amplitude order of the nonrecoverable creep compliance and phase angle. The results reveal that the evaporation process leads to oxidation and hardening of the residues. The hardening degree of the ASTM D7497-09 evaporation method is higher than that of the EN13074 evaporation method, and the hardening degree of the EN13074 evaporation method is higher than that of the direct heating method. The rheological and fatigue performances of the emulsified asphalt residues depend on the matrix asphalt. Moreover, the residue that was prepared from 70# asphalt has good high-temperature and fatigue properties, but it has higher temperature sensitivity and stress sensitivity.